Promoting children’s active engagement with storytelling and comics - Fernando, Sachini (My University, 2025)
Firstly, the thesis aims to present the pedagogical thinking process by illustrating activities as examples of active engagement in storytelling and comics. Cognitive, physical, cultural, and emotional aspects of learning were kept in mind to plan for active engagement. It is also important to note that these aspects are interconnected and mutually supportive in the examples shared. Secondly, the thesis attempts to support pedagogical ideas by referencing scientific articles to substantiate the ideas presented. Thirdly the thesis examines how stories and comics promote active engagement. Finally, the thesis discusses the challenges and limitations of keeping teachers and practitioners well-informed. Additionally, detailed explanations of activities, resources, sample works and comic artworks by preschool children are included in the appendix for reference and further understanding. During the literature review, the title and techniques are adjusted in response to critical comments obtained from a pair of university student’s presentations and illustrations created by a group of preschool children in a Finnish daycare context.
Keywords: storytelling, comics, active engagement, early childhood education, Finnish national core curriculum